2011
DOI: 10.1039/c0ja00245c
|View full text |Cite
|
Sign up to set email alerts
|

Multi-technique characterization of ancient findings from Gela (Sicily, Italy)

Abstract: In the present study we carried out an extensive non-destructive and micro-destructive surface investigation on ancient decorated Sicilian samples of cultural interest, using a combination of different spectroscopic methods. In particular, the elemental composition, obtained by a handheld XRF analyser, acted as a valuable guideline for subsequent targeted sampling actions, thus minimizing the sampling damage. Hence, some questions not answered by XRF measurements (identification of some pigments, preparation l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In order to preserve the integrity as well as the aesthetic value of artistic objects, micro-destructive and non-destructive techniques are preferred [5][6][7][8]. Each analytical method offers advantages and limitations according to the material under study, so multi-techniques approaches are usually adopted [9][10][11]. Among the various objects of artistic value, a large quantity, such as bowls, jewellery and stained glass windows, was created using glass as a raw material.…”
Section: Introductionmentioning
confidence: 99%
“…In order to preserve the integrity as well as the aesthetic value of artistic objects, micro-destructive and non-destructive techniques are preferred [5][6][7][8]. Each analytical method offers advantages and limitations according to the material under study, so multi-techniques approaches are usually adopted [9][10][11]. Among the various objects of artistic value, a large quantity, such as bowls, jewellery and stained glass windows, was created using glass as a raw material.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the elemental composition acquired by the portable XRF (PXRF) analyzer can provide valuable information for subsequent sampling operations, and then minimize the damage from aimless sampling. For example, Calva et al [235] applied PXRF technique to the analysis of colored fragments of plasters and floors collected from ancient Sicilian constructions. The results demonstrated that the mortars were mainly constituted of calcite in which the red or pinkish substrates were composed of iron oxides and ochres, while the white pigments were mainly composed of CaCO 3 .…”
Section: X-ray Fluorescence Spectroscopymentioning
confidence: 99%
“…The Cell_1 is 52 mm in diameter and 50 mm in height, providing an effective volume of c.a. v ¼ 60 cm 3 Fig. 1.…”
Section: Experimental Instrumentationmentioning
confidence: 99%